Phytochemical screening of Balinese grape (Vitis vinifera L. var. Alphonso Lavallee) peel extract: Resources local plant-based lessons in biology - Ida Ayu Manik Damayanti; Ni Wayan Sukma Antari (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
The utilization of local natural resources for contextual and practical-based learning is an innovative approach in biology education. This study aimed to conduct a phytochemical screening of Balinese grape (Vitis vinifera L. var. Alphonso Lavallee) peel extract and integrate the findings into plant-based biology lessons. A mixed-method approach with a one-group pretest–posttest design was applied. Phytochemical tests identified the presence of flavonoids, phenols, alkaloids, tannins, and terpenoids. The integration of results into laboratory-based lessons led to an increase in students’ average scores from 66.70 to 78.48, as well as improvement in laboratory skills, cultural awareness, and appreciation of local biodiversity. These findings demonstrate that Balinese grape peel extract is a valuable educational tool for enhancing understanding of secondary metabolites and promoting scientific literacy. The future impact of this research includes the potential for in vitro and in vivo studies to assess the extract’s biological activity, and the implementation of local plant-based learning models that support sustainable education and preservation of indigenous knowledge.Abstrak. Pemanfaatan sumber daya alam lokal untuk pembelajaran kontekstual berbasis praktikum merupakan pendekatan inovatif dalam pendidikan biologi. Penelitian ini bertujuan untuk melakukan skrining fitokimia kulit anggur Bali (Vitis vinifera L. var. Alphonso Lavallee) serta mengintegrasikan hasilnya ke dalam pembelajaran berbasis sumber daya tumbuhan lokal. Penelitian ini menggunakan metode campuran dengan desain pra-eksperimen one-group pretest–posttest. Skrining fitokimia dilakukan terhadap senyawa flavonoid, fenol, alkaloid, tanin, dan terpenoid melalui uji pereaksi spesifik. Hasil skrining menunjukkan adanya kelima senyawa aktif tersebut, Integrasi hasil ke dalam pembelajaran laboratorium meningkatkan nilai rerata siswa dari 66,70 menjadi 78,48, serta memperkuat keterampilan laboratorium, kesadaran budaya, dan apresiasi terhadap biodiversitas lokal. Temuan ini menunjukkan bahwa penggunaan ekstrak kulit anggur Bali dapat meningkatkan literasi sains dan pemahaman peserta didik terhadap metabolit sekunder. Dampak jangka panjang dari penelitian ini mencakup potensi pengembangan studi in vitro dan in vivo untuk mengeksplorasi aktivitas biologis ekstrak serta penerapan pembelajaran berbasis sumber daya lokal yang mendukung pendidikan berkelanjutan dan pelestarian kearifan lokal.